Characterization and functional analysis of peroxiredoxin 4 gene in the Neocaridina denticulata sinensis. Issue 122 (March 2022) - Wang, Ying; Zhang, Ruirui; Xu, Ce; Sun, Yuying; Zhang, Jiquan
Abstract: Peroxiredoxin (Prx) is an antioxidant protein family, which widely exists in organisms and plays an important role in innate immunity. In this study, the full-length cDNA of a Prx gene ( NdPrx ) was obtained from Neocaridina denticulata sinensis, which contains a 735 bp open reading frame (ORF) and encodes a polypeptide of 244 amino acids. It is inferred that the molecular weight of the encoded amino acid is 27261.20 Da and the theoretical isoelectric point is 6.16. Phylogenetic analysis shows that NdPrx and Prx4 have high homology, so it was named NdPrx4 . Multiple alignment analysis showed that the amino acid sequence of NdPrx4 had high homology with Prx4 of other species, and the similarity with Homarus americanus was the highest, 92.86%. Quantitative real-time PCR analysis showed that NdPrx4 was expressed in various tissues of N. denticulata sinensis, and the expression in ovary was the highest. It was speculated that NdPrx4 may be related to maternal immune function. Under the stimulation of Cu 2+, the expression of NdPrx4 reached the peak at 36 h, and showed a downward trend until 72 h, indicating that NdPrx4 may play an important role in the stress response of N. denticulata sinensis . Then, NdPrx4 was recombinantly expressed in E. coli, and its enzymatic characteristics of rNdPrx4 were detected. The result showed that the activity of rNdPrx4 was the highest at pH 5.0 and 55 °C. It was found that Mn 2+ and Ca 2+ can inhibit the activity of rNdPrx4, and Zn 2+ increases the activity of rNdPrx4. Highlights: The full-length cDNA sequence of NdPrx4 was cloned and analyzed. NdPrx4 was predominantly expressed in ovary of N. denticulata sinensis. NdPrx4 was upregulated after copper ion stimulation . NdPrx4 was recombinantly expressed and the enzymatic characterization was determined.